2000
DOI: 10.1161/01.str.31.6.1439
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Comparison of the Early Outcome of Angioplasty and Endarterectomy for Symptomatic Carotid Artery Disease

Abstract: Background and Purpose —Endoluminal treatment is being increasingly used for carotid artery disease. The aim of this study was to compare the stroke and death risk within 30 days of endovascular treatment or endarterectomy for symptomatic carotid artery disease. Methods —A systematic comparison of the 30-day outcome of angioplasty with or without stenting and endarterectomy for symptomatic carotid artery disease reported in single-center studies, publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
36
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(37 citation statements)
references
References 42 publications
0
36
0
1
Order By: Relevance
“…The combined stroke and death rate within 30 days of 6.4% in symptomatic patients is in the range of 7.8% found in a recent survey of the literature, in which most symptomatic patients had been treated with angioplasty alone. 5 Although a comparison between these 2 reviews should be made with caution because of the wide heterogeneity in patients and study designs, the similar complication rates indicate that the additional stent deployment does not increase clinically relevant thromboembolic complications. While this might appear self-evident, the insertion of a stent is associated with an increased occurrence of microembolic signal as detected by transcranial Doppler, 54 which could lead to more thromboembolic complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined stroke and death rate within 30 days of 6.4% in symptomatic patients is in the range of 7.8% found in a recent survey of the literature, in which most symptomatic patients had been treated with angioplasty alone. 5 Although a comparison between these 2 reviews should be made with caution because of the wide heterogeneity in patients and study designs, the similar complication rates indicate that the additional stent deployment does not increase clinically relevant thromboembolic complications. While this might appear self-evident, the insertion of a stent is associated with an increased occurrence of microembolic signal as detected by transcranial Doppler, 54 which could lead to more thromboembolic complications.…”
Section: Discussionmentioning
confidence: 99%
“…4 In contrast, a recent systematic comparison of the 30-day outcome of CAS and CEA for symptomatic CAD in single-center studies performed during 1990 -1999 revealed a significantly higher risk of stroke or death for CAS than for CEA. 5 Both this survey and CAVA-TAS elucidate the great challenges associated with the performance of trials comparing CEA with CAS. The field of endovascular therapy is subject to rapid technological advances.…”
mentioning
confidence: 99%
“…Recent studies demonstrated that CAS has comparable outcomes and complication rates with CEA [20, 21] despite the fact that CAS produces more emboli compared with CEA on TCD [4, 22] or silent strokes on MRI [23, 24]. CAS with the distal protection device had less clinical complications [7, 25] and emboli formation [26] than CAS without protection.…”
Section: Discussionmentioning
confidence: 99%
“…35 Since the year 2000, 7 studies have been published with larger sample sizes (mean, 222 patients; range, 99 to 528) and 14.9-month follow-up (range, 11.2 to 20 months). 36 -41 The reported 30-day stroke and death rates range from 1% to 4%, with early restenosis rates of 0.5% to 14% (Table 3).…”
Section: Discussionmentioning
confidence: 99%